Electronic health record evidence suggests undercoding, underrecognition, and low antifibrotic use in progressive pulmonary fibrosis - Bradley A. Sheffield; Brian J. Cassel; Apostolos Perelas; Patricia Sime; Peter Jackson (PLOS One, 2026)
Background Progressive pulmonary fibrosis (PPF) is a heterogeneous group of non-IPF ILDs characterized by fibrotic progression and poor prognosis. Antifibrotic therapies slow disease progression, yet widely variable real-world prevalence estimates suggest that PPF may be undercoded and potentially underdiagnosed. In preliminary TriNetX analyses using ICD-10 code J84.170, PPF prevalence was markedly lower than previous estimates. To explore a potentially undiagnosed and/or uncoded PPF cohort, we adapted a published PPF proxy algorithm and compared demographic, clinical, and treatment differences between formally coded patients and proxy-identified patients. Methods We conducted a retrospective cohort study using the TriNetX U.S. Collaborative Network from 2021 to 2024. Coded PPF was defined by J84.170, excluding IPF. Three proxy PPF cohorts—sensitive, specific, and strict—were adapted from Olson et al. using the closest available TriNetX variables, combining non-IPF ILD diagnoses with progression criteria. Prevalence, antifibrotic use, demographics, and ILD subtype distributions were compared. Outcomes included respiratory failure, death, and lung transplant. Odds ratios (ORs) and hazard ratios (HRs) were calculated. Propensity matching included age, sex, race, and BMI; balance was assessed using standardized mean differences (SMD < 0.10). Results Among 57,193,009 adults, coded PPF prevalence was 3.7 per 100,000 versus 250, 124, and 32 per 100,000 in the sensitive, specific, and strict proxy cohorts, respectively. Antifibrotic use was 18.3% in coded PPF, compared with 3.2% in the sensitive cohort (OR 0.15), 5.6% in the specific cohort (OR 0.34), and 8.6% in the strict cohort (OR 0.64). IPF treatment was higher than PPF treatment (28.5%; OR 1.97). Demographics and ILD subtype distributions were broadly similar, and clinical outcomes were comparable between coded and proxy cohorts. Relative to PPF, IPF had lower hazards of respiratory failure (HR 0.56) and death (HR 0.52), but higher transplant rates (HR 1.93). Conclusions Proxy-defined cohorts identified clinically similar but largely untreated populations, supporting the possibility of an uncoded and/or unrecognized PPF cohort. EHR-based proxy algorithms may serve as scalable screening tools to identify high-risk patients for further clinical evaluation. These findings should be interpreted cautiously given the use of EHR-derived proxy markers and evolving awareness and coding practices for PPF over time. Further validation with chart review and integrated clinical data is needed.